Promoting the Agriculture of Chiang Mai Local Community - Stiankong , Jatuporn (Community and Social Development Journal, 2020)
This research aims to study and develop the potentiality of agriculture of Chiang Mai communities. It is the qualitative research and were supported by quantitative analysis from primary data of 6 groups of agriculturists and willing to attend the project. All of these 6 groups have potentiality in which governmental organizations promoted agriculture in communities. SWOT analysis, participatory action research and Michael E. Porter’s diamond model were used in this study. Descriptive statistics and 6 dimensions were used to evaluate the achievement of the project in order to display and look for guidelines that government should promote agriculture in Chiang Mai communities to compete in ASEAN. The research found that the strengths of all these 6 groups were that members were capable and specialized in production, marketing, cultivating, processing and public relations. Their weaknesses were that they could not manage farm and areas of planting efficiently. They have less power to negotiate with middlemen. They however were supported in knowledge and budgets by both government and private organizations. Their threats were that it has a high competition in marketing both price and quantity and marketing lack of varieties. There are six items of guidelines to promote agriculture of governent in Chiang Mai communties to compete in ASEAN . The most important item was that government should promote budgets, knowledge, production , accounting and marketing.